2009
DOI: 10.1007/s00705-009-0533-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Bocavirus-2 in children with acute Gastroenteritis in South Korea

Abstract: Human bocavirus (HBoV)-2, a new parvovirus, has been identified in stool samples and is suggested to be one of the etiologic agents of acute gastroenteritis (GE). The purpose of this study was to investigate the prevalence of HBoV-2 in children with GE. Stool samples were collected from 358 children hospitalized with GE. HBoV-2 was detected in 3.6% of the patients. HBoV-2 was co-detected with other viral agents in 53.8% of the patients. These findings suggest that HBoV-2 may be an etiologic agent in GE, but fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 22 publications
7
48
1
Order By: Relevance
“…In this study, a similar detection rate for HBoV-1 was observed in both male and female children, which is in agreement with other studies conducted in other parts of the world , Han et al 2009). This finding reinforces data from previous investigations conducted in the region that show no difference in gastroenteric virus detection rates regardless of the children's gender (Camarota et al 1992, Borges et al 2006.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, a similar detection rate for HBoV-1 was observed in both male and female children, which is in agreement with other studies conducted in other parts of the world , Han et al 2009). This finding reinforces data from previous investigations conducted in the region that show no difference in gastroenteric virus detection rates regardless of the children's gender (Camarota et al 1992, Borges et al 2006.…”
Section: Discussionsupporting
confidence: 93%
“…HBoV detection in faecal samples from individuals with acute gastroenteritis has gained importance following the positive identification of bocavirus in faecal samples from individuals throughout the world (Albuquerque et al 2007, Lau et al 2007, Monteny et al 2007, Vicente et al 2007, Han et al 2009, Chow et al 2010, Kantola et al 2010, Jin et al 2011. In Brazil, only three studies have been published regarding HBoV detection in children with acute gastroenteritis (Albuquerque et al 2007, Santos et al 2010, Proença-Modena et al 2011 and this is the first study conducted in the Central-West Region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are confirmed by clinical observations indicating that the infection manifests as a respiratory condition. In contrast, hBoV2, hBoV3 and hBoV4 colonize the gastrointestinal tract; hBoV2 and possibly hBoV3 are associated with gastroenteritis [46,47]. Interestingly, hBoV2 is the only intestinal bocavirus isolated from a nasal swab; therefore it may be associated with respiratory diseases [48,49].…”
Section: Human Bocavirusmentioning
confidence: 99%